2013
DOI: 10.1063/1.4808346
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of photoexcited carriers and spins in InAsP ternary alloys

Abstract: A.; Magill, B. A.; Merritt, T. R.; et al., "Dynamics of photoexcited carriers and spins in InAsP ternary alloys," Appl. Phys. Lett. 102, 222102 (2013); http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Also, by fitting the experimental spectra via three different methods a 'hot' carrier temperature is associated with electrons only; all three methods yield similar 'hot' carrier temperatures. This observation suggest that narrow gap heterostructures [38,39] could be a good candidate for hot carrier absorbers [12,33,40,41].…”
Section: (B)mentioning
confidence: 78%
“…Also, by fitting the experimental spectra via three different methods a 'hot' carrier temperature is associated with electrons only; all three methods yield similar 'hot' carrier temperatures. This observation suggest that narrow gap heterostructures [38,39] could be a good candidate for hot carrier absorbers [12,33,40,41].…”
Section: (B)mentioning
confidence: 78%
“…Due to the low excitation intensities used, cooling excitons give rise to relatively small changes in the LO phonon occupation number such that hot phonon bottlenecking is unlikely. 10 In addition, this carrier migration between localized states may account for the long rise times in the x ¼ 0.40 TRPL spectra, depicted by the initial divergence from the fitted behavior. 36,37 Furthermore, the relaxation of cool excitons may also have to contend with localized states brought about by compositional disorder, which can conceivably account for the two-fold increase in s 2 for x ¼ 0.40 with respect to that for x ¼ 0.13.…”
Section: Resultsmentioning
confidence: 99%
“…6 Investigating the dynamics of carriers involved in radiative transitions in these alloys not only provides a means to assess and improve sample quality but also aids in the design and optimization of device structures. However, while the morphology and the electronic properties of InAsP have been extensively explored, [7][8][9][10][11][14][15][16][17]31 studies concerning optical characterization are limited. [14][15][16][17] Although there are a large number of optical studies involving quantum structures, 2,[18][19][20] alloy epilayers are more appropriate when considering fundamental optical transitions since confounding effects, such as quantum confinement and interface-related defects, are avoided.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study concluded that interference effects are crucial in the micro-Raman spectroscopy of graphene and must be included in analysis when extracting various material information from the spectra [31]. As we move into ternary and quaternary alloys and magnetically doped novel materials for ambient operable devices that successfully exploit charge and spin mobility, experimenters have come to avoid any such effects in the measurement scheme [32].…”
Section: Introductionmentioning
confidence: 99%